(3TQM dGejI GdYLes - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s; (3GdWZQGFj , GdMSjf Hf Ydj Hf eMeO Hf YHO GdUeO GdCUHgGfj GdWZQGfj, eDjO GdOjf CHh ESeGYjd,J (B513 (3g` s ((3MeRg Hf bGSe Hf GdTgGHi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi TQM UOQ ef JCOH , hQaY bOQ ef JCgd ddYde hJCgH aEf GdbUjOg GdehSheg HdGejg GdYLe QMe Gddg fGXe YbOgG s
(3BNQgG (B:s
(3hda ai GdHQOg CYWGag MJi jWjH GdfTQ ai dag Je GdcJGH HMeO Gddg s
(3Vef eLehY s
(3GdUaMI GdChdi Hbde eNGdas
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs